Occupational exposures in healthcare workers in University Hospital Dubrava--10 year follow-up study - Serdar, Tihana; Derek, Lovorka; Unić, Adriana; Marijancević, Domagoj; Marković, Durda; Primorac, Ana; Petrovecki, Mladen (Central European journal of public health, 2013)
Occupational hazardous exposure in healthcare workers is any contact with a material that carries the risk of acquiring an infection during their working activities. Among the most frequent viral occupational infections are those transmitted by blood such as hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV). Therefore, they represent a significant public health problem related to the majority of documented cases of professionally acquired infections. Reporting of occupational exposures in University Hospital Dubrava has been implemented in connection with the activity of the Committee for Hospital Infections since January 2002. During the period of occupational exposures' monitoring (from January 2002 to December 2011) 451 cases were reported. The majority of occupational exposures were reported by nurses and medical technicians (55.4%). The most common type of exposure was the needlestick injury (77.6%). 27.9% of the accidents occurred during the blood sampling and 23.5% during the surgical procedure. In 59.4% of the exposed workers aHBs-titer status was assessed as satisfactory. Positive serology with respect to HBV was confirmed in 1.6% of patients, HCV in 2.2% of patients and none for HIV. Cases of professionally acquired infections were not recorded in the registry. Consequences of the occupational exposure could include the development of professional infection, ban or inability to work further in health care services and last but not least a threat to healthcare workers life. It is therefore deemed necessary to prevent occupational exposure to blood-borne infections. The most important preventive action in respect to HBV, HCV and HIV infections is nonspecific pre-exposure prophylaxis.
Keywords: hepatitida C; Virus Diseases; Infectious Disease Transmission, Patient-to-Professional; Health Personnel; Occupational Exposure; patogeny v krvi; HIV Infections; virové nemoci; bodné poranění jehlou; pracovní expozice; řízení rizik; Croatia; Blood-Borne Pathogens; přenos infekce z pacienta na zdravotnického pracovníka; HIV infekce; Hepatitis B; zdravotnický personál; nemocnice univerzitní; lidé; Humans; Hepatitis C; hepatitida B; Risk Management; Hospitals, University; Needlestick Injuries; Chorvatsko